2021
DOI: 10.1002/onco.13743
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Apolipoprotein A1 Ratio Predicted Overall Survival in Hepatocellular Carcinoma Receiving Transarterial Chemoembolization

Abstract: Purpose. To investigate the predictive capability of Neutrophil-to-Apolipoprotein A1 ratio (NAR) for predicting overall survival (OS) among hepatocellular carcinoma (HCC) patients receiving transarterial chemoembolization (TACE). Patients and methods. We investigated the clinical features of 554 HCC patients receiving TACE and assessed NAR's predictive value for OS with 222 consisting the discovery cohort and 332 consisting the validation cohort. The association of NAR with circulation LOX-1 + polymorphonuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Although the underlying mechanism of lipid profile alterations with the MACROD2 rs6110695 A>G polymorphism cannot be elucidated by our findings, a previous study reported that a high WBC to apolipoprotein A‐I ratio is significantly related to long‐term adverse prognosis in CVD 31 . Similarly, the neutrophil to apolipoprotein A‐I ratio was identified as a novel predictor for overall survival in patients with hepatocellular carcinoma 32 . Maintenance of a high WBC to apolipoprotein A‐I ratio seems to be related to poor prognosis of diseases; hence, having the rs6110695 AG genotype is somewhat unfavorable.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Although the underlying mechanism of lipid profile alterations with the MACROD2 rs6110695 A>G polymorphism cannot be elucidated by our findings, a previous study reported that a high WBC to apolipoprotein A‐I ratio is significantly related to long‐term adverse prognosis in CVD 31 . Similarly, the neutrophil to apolipoprotein A‐I ratio was identified as a novel predictor for overall survival in patients with hepatocellular carcinoma 32 . Maintenance of a high WBC to apolipoprotein A‐I ratio seems to be related to poor prognosis of diseases; hence, having the rs6110695 AG genotype is somewhat unfavorable.…”
Section: Discussionmentioning
confidence: 65%
“… 31 Similarly, the neutrophil to apolipoprotein A‐I ratio was identified as a novel predictor for overall survival in patients with hepatocellular carcinoma. 32 Maintenance of a high WBC to apolipoprotein A‐I ratio seems to be related to poor prognosis of diseases; hence, having the rs6110695 AG genotype is somewhat unfavorable.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, relevant studies have shown that combining apoA-I and neutrophils may be a practical prognostic index for HCC patients undergoing transcatheter arterial chemoembolization. By studying the prognostic value and potential immune mechanism of the neutrophil apolipoprotein A ratio (NAR) in HCC patients receiving transcatheter arterial chemoembolization in two independent cohorts, researchers found that NAR showed prognostic performance similar to that obtained with the Cancer of the Liver Italian Program score, and when the score was adjusted by considering the NAR, the prediction for overall survival and survival rate at a specific time point was more accurate ( Chen et al, 2021 ). The generation of PMNs requires long-range intercellular communication continuously mediated by soluble or membrane-binding factors on primary tumours ( Liu and Cao, 2016 ; Peinado et al, 2017 ), and intercellular communication synapsis formation and timing are controlled by cholesterol.…”
Section: Lipid Metabolism and Tumor Immune Microenvironmentmentioning
confidence: 99%
“…Polymorphonuclear myeloid-derived suppressor cells are pathologically activated neutrophils that are essential for regulating the immune response to cancer. Lipid metabolism is a crucial regulator of PMN-MDSCs ( Veglia et al, 2019 ; Chen et al, 2021 ). A study found that fatty acid transporter 2 (FATP2) controlled the inhibitory activity of PMN-MDSCs.…”
Section: Lipid Metabolism and Tumor Immune Microenvironmentmentioning
confidence: 99%
“…NAR has a predictive value for long-term tumour disease prognosis [ 15 , 35 ]. However, data on NAR’s impact on the long-term prognosis of AF patients are limited.…”
Section: Discussionmentioning
confidence: 99%